The Syllabification of High Vowels in the Kerinci Language: An Autosegmental Phonological Analysis: Penyukuan Vokal Tinggi dalam Bahasa Kerinci: Analisis Teori Fonologi Autosegmental (Jurnal Bahasa, 2022)
The aim of this article is to explain the syllabification of high vowels /i/ and /u/ at the nucleus position in the Kerinci language. In this language, the high vowels /i/ and /u/ at the nucleus position will undergo changes—for example, /i/, /u/, /is/ and /us/ will be realized as [aj], [aw], [ajh] and [awh]. In order to explain the phonological processes, each problem was analyzed using the theory of autosegmental phonology (Goldsmith, 1976, 1990). There are three processes involved in the theory, namely linking, delinking and features spreading. The phonological modifications involving the high vowels can be adequately explained based on the process of syllabification that is couched in the CV skeletal model of McCarthy (1981). The data for this study were obtained through three different methods, namely library research, observation and interviews. The instruments used in this study were a recorder, questionnaires and notebooks. The informants selected for this study comprised five men and women who are aged 50 years and above, who are native speakers of Kerinci Semerap dialect, and were born in Kabupaten Kerinci, West Sumatera, Indonesia. However, they have been living in Kampung Batu 21 Sungai Lui, Hulu Langat, Selangor, for more than 30 years. The finding showed that the high vowels /i/ and /u/ at the nucleus of word final syllable are linked to the coda nodes and surfaces as the glides [j] and [w]. Thus, the analysis of the syllabification of high vowels at the coda position explains the application of vowel [a] in the output of words such as [mã.taj] “dead”, [sa.taw] “one”, [tu.lajh] “write” and [lu.rawh] “straight” based on the CV skeletal model of McCarthy (1981). Keywords: Kerinci language, syllabification of high vowels, coda, syllable stucture, autosegmental phonologyFull text: PDF